An in-Depth Analysis of Students’ Mathematical Connections in the Context of the Pythagorean Theorem - Tita Azzahra, Sevilla; Octafian, Allysa Ramadhani; Rahmah, Padilah; Fajar, Cerio Rahmat; Suripah (Indonesian Journal of Teaching and Learning, 2025)
Purpose – Mathematical connection ability is a high-order thinking skill necessary for linking mathematical concepts across topics, disciplines, and real-life contexts. Preliminary observations suggest that many students struggle to establish these connections, particularly when learning the Pythagorean Theorem. Methodology – This study employed a qualitative descriptive research design using a case study method. The sample consisted of 22 students, with four participants purposively selected to represent varying levels of mathematical connection ability. Data were collected through a six-item written test developed based on NCTM indicators and supported by semi-structured interviews for triangulation. Data were analyzed qualitatively to identify patterns in students' mathematical connection performance. Findings – The study found that students generally demonstrated high levels of mathematical connection ability, with a mean score of 70.26%. Most students were able to connect mathematical concepts across different topics and disciplines. However, they encountered difficulties in applying mathematical ideas to real-life situations. These findings highlight the gap between theoretical understanding and practical application. Novelty – This study contributes to the literature by providing in-depth insights into students’ levels of mathematical connection ability, particularly in contextual problem-solving involving the Pythagorean Theorem. Significance – The findings are beneficial for mathematics educators, curriculum designers, and educational policymakers to enhance instructional strategies and support applied mathematical thinking in students.